2020
DOI: 10.3390/nu12051291
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hesperidin on Systemic Immunity of Rats Following an Intensive Training and Exhausting Exercise

Abstract: Intensive training and exhausting exercise can disrupt innate and acquired immunity. The flavanone hesperidin has shown immunomodulatory properties in physiological and some pathological conditions, and positive effects on exercise-induced oxidative stress. Nevertheless, it remains uncertain whether it also prevents exhausting exercise-induced immune alterations. The aim of this study was to establish the effect of oral hesperidin supplementation on the systemic immune system in rats following an intensive tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…The results of another study indicate the beneficial effects of citrus flavanones in the old-aged rat liver, where naringenin and hesperidin prevented the age-linked decrease of catalase, superoxide dismutase and glutathione reductase [66]. Hesperidin demonstrated antioxidant activity in rats after an intensive training program, and attenuated the secretion of cytokines by stimulated macrophages [67,68]. The administration of hesperetin has been shown to significantly reduce the levels of myeloperoxidase, malondialdehyde (a marker of lipid peroxidation) and inflammation in experimental models of colitis [69] and hepatic trauma [70].…”
Section: Antioxidant Activitymentioning
confidence: 94%
“…The results of another study indicate the beneficial effects of citrus flavanones in the old-aged rat liver, where naringenin and hesperidin prevented the age-linked decrease of catalase, superoxide dismutase and glutathione reductase [66]. Hesperidin demonstrated antioxidant activity in rats after an intensive training program, and attenuated the secretion of cytokines by stimulated macrophages [67,68]. The administration of hesperetin has been shown to significantly reduce the levels of myeloperoxidase, malondialdehyde (a marker of lipid peroxidation) and inflammation in experimental models of colitis [69] and hepatic trauma [70].…”
Section: Antioxidant Activitymentioning
confidence: 94%
“…Regarding flavonoid supplementation, a previous study reported a 5% increase in absolute power output in a 10-min time trial (TT) after four weeks of 2S-hesperidin intake (500 mg) in cyclists [13]. Other authors have also reported performance improvements (time until exhaustion~58%) in animals [17,18]. Currently there are no other studies that analyzing the effects of chronic hesperidin intake on performance.…”
Section: Incremental Testmentioning
confidence: 99%
“…This study also found an improvement in endogenous antioxidant enzymes, such as reduced glutathione (GSH), oxidized glutathione (GSSG) and GSH:GSSG ratio. In the same line, a recent study in trained animals reported that intake of hesperidin for 4 weeks improved performance and prevented immune alterations induced by exhausting exercise [15]. Recently, one parallel-group study has shown improvements in the time until exhaustion (58%) on maximal exercise test at 3 weeks of a 5-week chronic supplementation of 2S-hesperidin (200 mg/kg), but not in placebo group [16].…”
Section: **Insert Figure 1**mentioning
confidence: 96%
“…In addition, performance improvements have also been seen in animals following chronic intake of hesperidin and hesperetin (hesperidin metabolite) [13,15,16].…”
Section: Wingate Testmentioning
confidence: 99%
See 1 more Smart Citation